Responsibility of Cooperatives as Public Transportation Operators for the JakLingko Microtrans Accident on Route 17 Pulo Gadung – Senen - Simanjuntak, Elsa Maria S G (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
accidents in Jakarta, one of which is the Mikrotrans JakLingko Route 17 Pulo Gadung–Senen accident caused by driver negligence. The main issues examined are: What is the form of responsibility of Koperasi as the operator of Mikrotrans JakLingko toward the victims of the Route 17 Pulo Gadung–Senen accident caused by the driver; and what obstacles does Koperasi face as the operator of Mikrotrans JakLingko in fulfilling its responsibility toward the victims of the Route 17 accident caused by the driver. This study employs a normative juridical method with a descriptive approach, using secondary data and primary data supported by interviews, analyzed qualitatively with deductive reasoning. The findings indicate that Koperasi, as a public transportation operator, bears legal responsibility for the actions of its employed drivers, in accordance with Articles 192 and 189 in conjunction with Article 309 of Law No. 22 of 2009. The main obstacle lies in the absence of sufficient funds to fully compensate the victims.